MAIN FACTORS DETERMINING THE POSITIVE IMAGE OF PRIVATE EDUCATIONAL INSTITUTIONS (Marketing Journal, 2025)
This article analyzes the factors influencing the "positive image" of private schools, and formulates and tests a number of hypotheses based on the total number of randomly selected respondents.
Keywords: factor; image; school; private school; education; service; quality; respondent